Insights into high mobility group A (HMGA) proteins from Poaceae family: An in silico approach for studying homologs. (August 2020) - Pal Negi, Archana; Singh, Ratnesh; Sharma, Anupma; Negi, Vishal Singh
Graphical abstract: Highlights: Three major evolutionary clades of Poaceae HMGAs were identified. Poaceae HMGAs from all the clades, except clade 2 HMGAs, were identified to lack the high-affinity type-I DNA-binding domain. No. of AT-hook (ATH) motif in Poaceae ranges from 3 to 5. The C-terminal tail following the last ATH in Poaceae HMGAs is significantly smaller compared to that of mammalian HMGAs. The length of the C-terminal tail following the last ATH is smallest and highly conserved in clade 2 HMGAs. Abstract: High mobility group (HMG) proteins are the major architectural proteins. Among HMG proteins, High Mobility Group A (HMGA) is characterized by AT-hook (ATH) motifs, which have an affinity for AT-rich DNA. In this study, we characterized the plant HMGAs from the Poaceae family using in silico methods. The protein sequences for rice HMGAs were retrieved and the corresponding orthologs from grasses were extracted. The phylogenetic analysis identified three major evolutionary clades of grass HMGAs and their ATH motif analysis revealed that HMGAs from clade 1 and 2, except for clade 2 HMGAs, are devoid of high-affinity DNA-binding domain. The clade 2 HMGAs also displayed a highly conserved length of all the spacers and the length of the C-terminal tail following the last ATH. Moreover, the C-terminal tail in clade 2 HMGAs is smaller than HMGAs from any other clade. Unlike clade 2, other clades of Poaceae HMGAs displayed high variability in the length of spacers. Despite several differences among HMGAs of different clades in Poaceae, the H1/H5 domain was found to be highly conserved. This study has revealed the detailed analyses of Poaceae HMGAs and it will be useful for further investigation aiming at the determination of precise biological functions and molecular mechanisms of grass HMGAs.